Acquisition of research skills by in training teachers during final degree projects - Calisto-Alegría, Carla (Revista Complutense de Educación, 2021)
Introduction Investigative skills are part of the graduation profiles, curricula and subject programs of the initial teacher training courses in Chile. They suggests the importance of developing methods and strategies for their didactic treatment. This research describes the interactions observed in an undergraduate seminar course for Language and Literature teachers in training. Method This is an ethnographic study in which class observations of an undergraduate seminar course were used together with participants’ focus groups. For the analysis, we used NVivo software. Results The main results show that, although the interactions favor the acquisition of research skills, the students do not have enough autonomy to initiate - and maintain - the interactions. This may affect the development of their communicative and research skills. Simultaneously, students agree that their training in research skills is linked to the development of attitudes. Discussion The discussion leads to the conclusion that the Graduate Seminar should be a place of trust, responsibility, equality and self-regulation in order to promote interaction, which is fundamental for the development of research skills.